Pengaruh Kompetensi dan Motivasi Terhadap Kinerja di Dinas Perhubungan Kabupaten Magetan - Patehurohmah, Patehurohmah (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2024)
This Study Evaluates The Influence Of Competence And Motivation On Employee Performance At The Department Of Transportation In Magetan Regency. Human Resources Play A Crucial Role In Every Organization, Whether Large Or Small, As They Are Responsible For All Ongoing Activities. Effective Human Resource Management Is Essential For Achieving Organizational Goals, Acting As A Thinker, Consultant, And Facilitator. The Quality Of Human Resources Can Be Assessed Through Employee Performance, Which Is Significantly Influenced By Their Competence And Motivation Levels. The Department Of Transportation In Magetan Regency Faces Challenges Related To Employee Competence. Observations Reveal That The Lack Of Competence Stems From The Reassignment Of Employees From Non-Technical Backgrounds, The Hiring Of Contract Workers With Non-Technical Education, And The Transfer Of Leaders Or Staff With Technical Certifications. These Conditions Lead To Low Productivity And Professionalism Among Employees. The Study Finds A Significant Relationship Between Competence And Work Motivation On Employee Performance At The Department Of Transportation In Magetan Regency. Therefore, Enhancing Employee Competence And Motivation Is Crucial For Improving Overall Organizational Performance.